Consistent, multi‐instrument single tube quantification of CD20 in antibody bound per cell based on CD4 reference. Issue 2 (6th July 2015) - Degheidy, Heba; Abbasi, Fatima; Mostowski, Howard; Gaigalas, Adolfas K.; Marti, Gerald; Bauer, Steven; Wang, Lili
Abstract : Detecting changes in the expression levels of cell antigens could provide critical information for the diagnosis of many diseases, for example, leukemia, lymphoma, and immunodeficiency diseases, detecting minimal residual disease, monitoring immunotherapies and discovery of meaningful clinical disease markers. One of the most significant challenges in flow cytometry is how to best ensure measurement quality and generate consistent and reproducible inter‐laboratory and intra‐laboratory results across multiple cytometer platforms and locations longitudinally over time. In a previous study, we developed a procedure for instrument standardization across four different flow cytometer platforms from the same manufacturer. CD19 quantification was performed on three of the standardized instruments relative to CD4 expression on T lymphocytes with a known amount of antibody bound per cell (ABC) as a quantification standard. Consistent and reliable measures of CD19 expression were obtained independent of fluorochrome used demonstrating the utility of this approach. In the present investigation, quantification of CD20 relative to CD4 reference marker was implemented within a single tube containing both antibodies. Relative quantification of CD20 was performed using anti‐CD20 antibody (clone L27) in three different fluorochromes relative to anti‐CD4 antibody (clone SK3). Our results demonstrated that cell surface marker quantification can be performed robustly using the single tube assay format with novel gating strategies. The ABC values obtained for CD20 expression levels using PE, APC, or PerCP Cy5.5 are consistent over the five different instrument platforms for any given apparently healthy donor independent of the fluorochrome used. © 2015 International Clinical Cytometry Society